Detection method for anti-cracking performance of water-based automobile inner plate surface paint and application of detection method

By simulating on-site conditions to detect the flash dry solids of the water-based car interior panel topcoat, the problem of wet film crack resistance detection is solved, and the rapid and accurate evaluation of the performance of water-based car interior panel topcoat is achieved, reducing the rework during construction Risk ensures the stability of product performance.

CN119310266APending Publication Date: 2025-01-14NIPPON PAINT GUANGZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310846154.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art lacks effective methods to detect the wet film resistance of water-based automotive interior panel topcoat, which leads to prone to paint film cracking problems during construction, affecting product performance and production efficiency.

Method used

By simulating on-site spraying conditions, the flash dry solids of the coating to be tested under different preheated flash dry conditions were measured, its crack resistance was evaluated, and the crack limit was tested by changing the spray film thickness, providing a water-based automotive inner panel surface Method for detecting anti-cracking performance of paint.

Benefits of technology

This method can quickly and accurately judge the crack resistance of water-based automobile inner panel topcoat, help develop and design stronger products, reduce the risk of rework during on-site construction, and ensure stable construction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119310266A_ABST
    Figure CN119310266A_ABST
Patent Text Reader

Abstract

The invention provides a method for detecting the anti-cracking performance of water-based automobile inner plate surface paint and application of the water-based automobile inner plate surface paint. The detection method comprises the following steps: S1, taking a to-be-tested plate, measuring the mass of the test plate, recording the mass as m1, and pasting an adhesive tape on the peripheral edge of the test plate; s2, spraying to-be-detected water-based automobile inner plate surface paint on the surface of the test plate to a target film thickness; s3, after spraying is completed, natural leveling is conducted, and then the to-be-detected water-based automobile inner plate face paint is preheated and subjected to flash drying; s4, after flash drying is finished, the adhesive tape on the test plate is torn off, and the mass of the test plate is measured and recorded as m2; and S5, drying the test panel, measuring the mass of the test panel after drying, recording the mass as m3, and calculating the flash-dry solid NV of the water-based automobile inner panel finish paint to be measured by adopting a formula # imgabs0 #.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating performance detection, and specifically comprises a detection method for the anti-cracking performance of water-based automobile inner panel topcoat and an application thereof. Background Art

[0002] With the rapid economic growth, family cars have become mass consumer goods entering thousands of households, and my country's total automobile production and sales have jumped to the first place in the world. The rapid development of the automobile industry has also greatly driven the development of automobile painting technology. The current mainstream spraying processes are 3C1B, 3C2B, IPP and 4C3B. In addition, due to the rapid development of the automobile industry and consumption upgrades, the color of the car body has become increasingly diversified, highlighting the trend of fashion and personalization. In order to adapt to the needs of market competition and catch up with new trends, major automobile manufacturers are constantly working hard to improve the decorativeness of the car's appearance. The car paint film presents high gloss, high vividness, multi-colorization, high three-dimensional sense, etc. Therefore, the car topcoat has also been upgraded from the traditional single-layer paint to a double-layer paint with high vividness and three-dimensional sense, and the clearcoat has also been upgraded to matte varnish or color varnish. It can be seen that the coating of the car's outer panel has always been the focus of car painting.

[0003] However, as part of the car body, the car inner panel also has the needs of protection and decoration, especially the area not covered by the interior parts. Inner panel spraying is also one of the indispensable links in the car original paint painting.

[0004] Unlike the coating of the outer panels of automobiles, the inner panel coating has different application scenarios, so the color, appearance and performance requirements are not as high as those of the outer panel coating. Generally, it is only required to cover the bottom defects, and there are no pinholes, sagging, loss of gloss, blowing, cracking and other paint film defects. In addition to the 3C2B process, in order to save costs, the inner panel is generally not sprayed with intermediate coating, and only the inner panel topcoat and varnish are sprayed. Under normal circumstances, the construction film thickness of the outer panel topcoat is between 10-20μm. In order to ensure that the inner panel topcoat can fully cover the bottom defects (such as particles, paint mist, etc.), the inner panel topcoat is usually thicker, especially for colors with poor hiding power. In addition, the color, appearance and performance requirements of the inner panel paint film are not as strict as those of the outer panel, and the film thickness fluctuates relatively greatly, and there are local thickening situations. In view of this situation, for the inner panel topcoat, especially the topcoat with less metallic pigment content, it is required to ensure that the construction film thickness is at least 20μm or more without paint film defects, so as to ensure that the on-site use requirements are met and the risk of rework is reduced.

[0005] With the continuous advancement of the low-carbon and environmental protection concept in the whole society, except for the clearcoat, the original midcoat and topcoat of domestic automobiles have basically achieved water-based. Since water-based paint contains a lot of water, whether it is the outer panel or the inner panel, after the water-based topcoat is sprayed, it must be preheated and flashed at low temperature to evaporate most of the water in the paint film to ensure a good match with the solvent-based clearcoat, so as to obtain the best appearance and paint film performance. Therefore, the flash-drying solid dehydration rate of water-based automobile coatings is very important. The more common preheating and flashing conditions on site are 80℃×5min, and the flash-drying solids are usually above 80%. The preheating temperature of the inner panel is relatively lower, and the flash-drying solids are relatively low. If the preheating and flashing of the water-based automobile inner panel topcoat is insufficient, the flash-drying solids are low, which is easy to cause the paint film and the varnish layer to lose gloss, and in severe cases, it will also cause the paint film to crack.

[0006] In the actual construction process, it is more common to spray the inner panel paint first, then spray the outer panel paint. After the inner and outer panel paint is completed, it will enter the low-temperature oven for preheating and dehydration before the varnish is applied. Due to the complex internal structure of the car, there are many cavities, especially at the position of the A-pillar. After the inner panel is sprayed with topcoat, the door will be closed for spraying the outer panel, and the position of the groove will form a relatively closed space. Due to the slow temperature rise inside the car, some areas, especially the cavity position forming a closed space, are prone to low flash-dry solids due to low preheating temperature. In addition, in order to prevent the paint mist from splashing on the outer panel during the spraying process of the inner panel paint and causing pollution, the spraying of the inner panel paint is generally sprayed with a low atomizer, resulting in poor atomization of the inner panel paint, which leads to a high moisture content after the inner panel paint forms a coating film. Therefore, due to the relatively thick film thickness of the inner panel paint, the relatively poor spray atomization conditions and insufficient preheating flash drying, it is easy to cause low flash-dry solids. After spraying the varnish, the varnish will solidify during the high-temperature baking process, which will cause the surface of the topcoat to shrink. The water-based automotive interior panel paint has a low flash-dry solid content and relatively large internal fluidity, which will cause cracks on the surface of the paint film.

[0007] Since the cracking of the paint film is related to the tensile strength of the paint film, the industry currently has flexibility, cupping resistance or impact resistance tests related to the tensile strength of the paint film, but the paint film needs to be dried before testing. There is currently no effective method to test the cracking resistance of the wet film. In view of this, it is necessary to provide a simple, fast and accurate method for testing the cracking resistance of water-based automotive interior panel topcoats, so as to understand the cracking resistance of the coating to be tested in advance, and to more accurately carry out product development and design and early prevention of water-based automotive interior panel topcoats with strong cracking resistance, to ensure the construction performance of the product on site. Summary of the invention

[0008] In view of the above-mentioned problems existing in the prior art, an object of the present invention is to provide a method for detecting the anti-cracking performance of water-based automobile inner panel topcoat. The method for detecting the anti-cracking performance of water-based automobile inner panel topcoat described in the present invention ensures that the spraying parameters and spraying conditions of the paint to be tested are consistent with those on site, can simulate the spraying of water-based automobile inner panel topcoat on site to the greatest extent, and can more accurately evaluate the construction performance of the paint to be tested on site. At the same time, by measuring the flash-dried solid content and the state of the composite coating under different preheating flash-drying conditions after the paint to be tested reaches the target construction film thickness, the anti-cracking ability of the water-based automobile inner panel topcoat to be tested can be directly evaluated by testing the flash-dried solid content, and the cracking limit of the paint to be tested can also be tested by changing the sprayed film thickness.

[0009] Another object of the present invention is to provide an application of the above-mentioned detection method in judging the anti-cracking performance of water-based automobile inner panel paint.

[0010] To achieve the above first object, the technical solution adopted by the present invention includes:

[0011] The present invention discloses a method for detecting the anti-cracking performance of water-based automobile inner panel topcoat, comprising the following steps:

[0012] S1: Take the board to be tested and measure the mass of the test board, recorded as m 1 , stick tape on the edges of the test plate;

[0013] S2: Spray the water-based automotive interior panel topcoat to be tested on the surface of the test panel to the target film thickness;

[0014] S3: After spraying, the paint will level naturally, and then the water-based automotive interior panel topcoat to be tested will be preheated and flash-dried;

[0015] S4: After flash drying, tear off the tape on the test board and measure the mass of the test board, recorded as m 2 ;

[0016] S5: Dry the test plate. After drying, measure the mass of the test plate, which is recorded as m 3 , using the formula Calculate the flash-dry solids NV of the water-based automotive interior panel topcoat to be tested.

[0017] Furthermore, the target film thickness is 18-26 μm.

[0018] Furthermore, the natural leveling time in step S3 is 2-5 minutes.

[0019] Furthermore, the temperature of the preheating flash drying is 40-60° C., and the time of the preheating flash drying is 2-3 minutes.

[0020] Furthermore, in step S5, the drying condition is (140-160)°C×(15-30)min.

[0021] Furthermore, the material of the test plate is selected from one of a hearing plate, an electrophoresis plate, a mid-coated plate, a cold-rolled steel plate and a tinplate plate.

[0022] Furthermore, the size of the test plate is (70-100) mm*(150-200) mm.

[0023] Furthermore, the detection method also includes determining whether the anti-cracking performance of the water-based automobile interior panel topcoat to be tested meets the on-site construction process requirements through the flash-dried solid content NV.

[0024] Further, the determination is:

[0025] When the flash-dry solid content is less than 60%, the water-based automotive inner panel topcoat to be tested has at least one of cracking, gloss loss, and pinholes, and it is determined that the anti-cracking performance of the water-based automotive inner panel topcoat to be tested does not meet the on-site construction process requirements;

[0026] When the flash-dry solid content is ≥60%, there is no cracking, gloss loss or pinholes in the tested water-based automobile inner panel paint, and it is determined that the anti-cracking performance of the tested water-based automobile inner panel paint meets the on-site construction process requirements.

[0027] To achieve the above second purpose, the technical solution adopted by the present invention includes:

[0028] The present invention discloses an application of the above-mentioned detection method in judging the anti-cracking performance of water-based automobile inner panel topcoat.

[0029] Beneficial effects of the present invention:

[0030] The present invention provides a method for detecting the anti-cracking ability of water-based automobile inner panel paint. The method highly simulates the low-atomization spraying conditions and insufficient flash drying preheating conditions of water-based automobile inner panel color paint on site. By measuring the flash drying solid content of water-based automobile inner panel paint, the anti-cracking ability of water-based automobile inner panel paint to be used in the automobile painting line can be directly, quickly and accurately judged. For products that crack below the target film thickness, the spray film thickness can be reduced according to the method of the present invention to test the cracking limit. For products with a lower cracking limit, the product can be improved or an on-site adjustment plan can be prepared according to the actual situation to ensure stable on-site construction. DETAILED DESCRIPTION

[0031] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The reason for the cracking of the inner panel of the car is that the paint is not fully dried in the preheating flash stage, the paint film has a high moisture content, the flash-dried solid content is low, the paint film still has a certain fluidity, and the curing shrinkage stress of the upper layer of paint easily pulls the bottom layer of paint and causes cracking. Therefore, based on this reason, the inventor studied whether the anti-cracking performance of the automotive inner panel topcoat can be predicted by measuring the flash-dried solid content.

[0033] Since paint cracking of automobile paint film basically only occurs on the inner panel, and water-based paint has a relatively large water content, insufficient water evaporated during low-temperature preheating and flash drying, resulting in a higher probability of paint cracking of automobile paint film. To this end, the present invention provides a method for detecting the anti-cracking performance of water-based automobile inner panel topcoat, which can more realistically simulate the conditions of insufficient flash drying at the inner panel where paint cracking occurs at the painting site, detect and judge the anti-cracking performance and cracking limit of the topcoat to be tested, so as to improve or adjust the plan on site for products with lower cracking limits in advance through simulation experiments, and ensure stable construction on site.

[0034] The present invention discloses a method for detecting the anti-cracking performance of water-based automobile inner panel topcoat, comprising the following steps:

[0035] S1: Take the board to be tested and measure the mass of the test board, recorded as m 1 , stick tape on the edges of the test plate;

[0036] S2: Spray the water-based automotive interior panel topcoat to be tested on the surface of the test panel to the target film thickness;

[0037] S3: After spraying, the paint will level naturally, and then the water-based automotive interior panel topcoat to be tested will be preheated and flash-dried;

[0038] S4: After flash drying, tear off the tape on the test board and measure the mass of the test board, recorded as m 2 ;

[0039] S5: Dry the test plate. After drying, measure the mass of the test plate, which is recorded as m 3 , using the formula Calculate the flash-dry solids NV of the water-based automotive interior panel topcoat to be tested.

[0040] In this detection method, the anti-cracking performance and cracking limit of the topcoat to be tested can be judged by calculating the flash-drying fixed content of the topcoat to be tested. In a specific embodiment, in order to further verify the correlation between the flash-drying fixed content and the appearance of the paint film, a group of control plates can be added when the test plate is sprayed and prepared. The control plates are subjected to a complete paint film spraying process (including topcoat + varnish). After the whole set of paint film spraying is completed, the appearance of the paint film is observed, thereby confirming the correlation between the flash-drying fixed content and the appearance of the paint film, and verifying the accuracy of the detection method of the present invention. The specific operation steps can be:

[0041] S1: Take two identical test plates, numbered as test plate 1# and test plate 2#, with test plate 2# as the control plate, and measure the mass of test plate 1#, recorded as m 1 , stick tape on the edges of test plate 1#;

[0042] S2: Spray the water-based automotive interior panel topcoat to be tested on the surfaces of test plate 1# and test plate 2# respectively to the target film thickness;

[0043] S3: After spraying, the paint will level naturally, and then the water-based automotive interior panel topcoat to be tested will be preheated and flash-dried;

[0044] S4: After flash drying, tear off the tape on test plate 1# and measure the mass of test plate 1#, recorded as m 2 ;

[0045] S5: spray varnish onto test plate 2# and perform natural leveling, then dry test plates 1# and 2#;

[0046] S6: After drying, measure the mass of test plate 1#, recorded as m 3 , using the formula Calculate the flash-dry solids NV of the water-based automotive interior panel topcoat to be tested, and observe the paint film appearance of test panel 2#.

[0047] Furthermore, in the detection method, the target film thickness of the sprayed topcoat should be consistent with the coating site, which is 18-26 μm. In order to ensure that no paint film defects are generated during construction, it is usually appropriate to select more than 20 μm. After the drying in step S6 is completed, the final film thickness on the test plate 1# is measured using a film thickness meter to confirm the final film thickness.

[0048] Although the preheating flash drying conditions set for the inner panel during on-site spraying are consistent with those for the outer panel, in fact, the baking temperature of the inner panel is lower than the set temperature, and there is a risk of cracking, gloss loss, and pinholes in the paint film due to insufficient preheating flash drying conditions. In a specific embodiment, in order to better simulate the situation in which the inner panel of the automobile has limited water evaporation in the paint film due to insufficient preheating flash drying conditions during on-site construction, the present invention simulates the low preheating conditions of the inner panel coating on site by reducing the preheating flash drying temperature and time, and limits the preheating flash drying temperature in the detection method to 40-60°C and the preheating flash drying time to 2-3min, which are lower than the common preheating flash drying conditions of the outer panel of the automobile (80°C×5min). In this way, the on-site construction conditions of the inner panel of the automobile can be restored more realistically, and a paint film appearance closer to the actual can be obtained.

[0049] In the present invention, the varnish for spraying is a varnish product matched with the topcoat to be tested, that is, the product combination of topcoat + varnish during on-site construction is consistent.

[0050] Furthermore, in the present invention, the spraying conditions when spraying the topcoat or varnish to be tested are consistent with the spraying conditions during on-site construction, such as spraying method (manual spraying or machine spraying), number of spraying times, spraying parameters, spraying environment temperature and humidity, etc. This is because the spraying conditions have a great influence on the atomization of the coating to be tested. Improper settings will directly affect the test results and make it impossible to truly restore the on-site construction conditions.

[0051] Furthermore, the natural leveling time in step S3 should be consistent with the on-site construction. Exemplarily, the natural leveling time in step S3 is 3 minutes.

[0052] Furthermore, the natural leveling time in step S5 should be consistent with the on-site construction. Exemplarily, the natural leveling time in step S5 is 6 minutes.

[0053] Furthermore, the drying conditions in step S5 should be consistent with the on-site construction. In a specific embodiment, the drying conditions in step S5 are (140-150)°C×(15-30)min; illustratively, the drying conditions can be 140°C×20min, 150°C×20min, 140°C×30min, 150°C×30min, and so on.

[0054] Further, the material of the test plate is selected from one of a hearing board, an electrophoresis plate, a middle-coated plate, a cold-rolled steel plate and a tinplate plate; the size of the test plate is (70-100) mm*(150-200) mm; exemplarily, the test plate is one of a 70mm*150mm electrophoresis plate, a middle-coated plate or a tinplate plate, a 75mm*150mm electrophoresis plate, a middle-coated plate or a tinplate plate, a 70mm*200mm electrophoresis plate, a middle-coated plate or a tinplate plate, a 100mm*150mm electrophoresis plate, a middle-coated plate or a tinplate plate, and a 100mm*200mm electrophoresis plate, a middle-coated plate or a tinplate plate.

[0055] Furthermore, the observing the appearance of the paint film of the test plate 2# mainly includes: observing whether the paint film of the test plate 2# has cracks, gloss loss or pinholes.

[0056] Furthermore, the detection method also includes determining whether the cracking performance of the water-based automobile interior panel topcoat to be tested meets the on-site construction process requirements through the flash-dried solid content NV.

[0057] Further, the determination is:

[0058] When the flash-dry solid content is less than 60%, the water-based automotive interior panel topcoat to be tested has at least one of cracking, gloss loss, and pinholes, and it is determined that the cracking performance of the water-based automotive interior panel topcoat to be tested does not meet the on-site construction process requirements;

[0059] When the flash-dry solid content is ≥60%, there is no cracking, gloss loss or pinholes in the tested water-based automobile inner panel paint, and it is determined that the cracking performance of the tested water-based automobile inner panel paint meets the on-site construction process requirements.

[0060] The materials used in the embodiments of the present invention are as follows:

[0061] 1. 70*150mm tinplate;

[0062] 2. 1 / 10,000 analytical balance;

[0063] 3. Oven;

[0064] 4. Timer;

[0065] 5. Film thickness meter;

[0066] 6. Test paint:

[0067] 1) Nippon Paint's water-based automotive interior panel topcoat AR-2100NH-730 water-based color paint and its matching clearcoat MAC O-330CLEAR NH-730 (for environmental use);

[0068] 2) Nippon Paint's water-based automotive interior panel topcoat AR2000 040 color paint (GTMC) and its matching clearcoat MAC O-1820CLEAR;

[0069] 3) Nippon Paint's water-based automotive interior panel topcoat AR 3000 yellow baking topcoat (BAIC) and its matching clearcoat 2K high-solid clearcoat (BAIC);

[0070] 4) Nippon Paint's water-based automotive interior panel topcoat AR 2300 solid red (BACH) and its matching clearcoat MAC O-1700 clearcoat (BACH).

[0071] The condition parameters for spraying topcoat in the embodiment of the present invention are shown in Table 1:

[0072] Table 1

[0073]

[0074]

[0075] The condition parameters for spraying the matching varnish in the embodiment of the present invention are shown in Table 2:

[0076] Table 2

[0077] Atomizer ABB 1000 Bellows Model 65mm X1 vertical speed (m / min) 1.2 Grid(mm) 100 Steering air 1(Nl / min) 400 Steering air 2 (Nl / min) 200 Speed ​​(*1000U / min) 30 Voltage setting value (kV) 0 Spraying distance (mm) 220

[0078] Example 1

[0079] The anti-cracking ability detection method of the water-based automobile inner panel topcoat described in the present application is used to test the AR-2100NH-730 water-based paint to determine the anti-cracking performance of the AR-2100NH-730 water-based paint, which specifically includes the following steps:

[0080] S1: Take two identical test plates, numbered as test plate 1# and test plate 2#, and measure the mass of test plate 1#, recorded as m 1 , and stick high temperature resistant tape on the edges of test plate 1#;

[0081] S2: Use a spraying robot, set the spraying temperature, humidity and parameters to be consistent with the on-site, adjust the spraying flow rate, and spray AR-2100NH-730 water-based paint to 20μm on test panels 1# and 2# respectively;

[0082] S3: After spraying, the paint was leveled naturally for 3 minutes, and then placed in an oven to preheat and flash-dry the AR-2100NH-730 water-based paint at 40°C × 3 minutes, 50°C × 3 minutes, and 60°C × 3 minutes respectively;

[0083] S4: Take out the test board and cool it naturally at room temperature. At the same time, tear off the masking tape on the test board 1# and measure the mass of the test board 1#, which is recorded as m 2 ;

[0084] S5: Use a hand spray gun to spray the test coating on-site matching varnish MAC O-330 CLEAR NH-730 (for environmental use) on test plate 2# and allow it to flow naturally for 5 minutes;

[0085] S6: Dry test plate 1# and test plate 2# at 140°C for 20 min and take them out;

[0086] S7: Measure the mass of test plate 1#, recorded as m 3 , calculate the flash-dried solids NV of the coating to be tested:

[0087] S8: Use a film thickness meter to measure the film thickness of the water-based automotive interior panel topcoat to be tested on test plate 1# to confirm whether it is 20μm;

[0088] S9: Observe the appearance of the paint film of test plate 2# to check whether the paint film has cracks, gloss loss or pinholes, and confirm whether the anti-cracking performance of the tested coating meets the construction requirements.

[0089] Table 3 Test results of anti-cracking performance of AR-2100NH-730 water-based paint

[0090]

[0091]

[0092] Note: △ indicates abnormal paint film, O indicates normal paint film

[0093] Through the above experimental results, the lower the preheating temperature of AR-2100NH-730 water-based paint, the lower the flash-dry solid content, and the greater the risk of cracking in the paint film. After flash-drying at 60℃×3min, there is no risk of cracking when the film thickness of AR-2100NH-730 water-based paint inner plate is within 20μm.

[0094] Example 2

[0095] The method for detecting the anti-cracking ability of the water-based automobile inner panel topcoat described in the present application is used to test the AR2000 040 paint (GTMC) to determine the anti-cracking performance of the AR2000 040 paint (GTMC), which specifically includes the following steps:

[0096] S1: Take two identical test plates, numbered as test plate 1# and test plate 2#, and measure the mass of test plate 1#, recorded as m 1 , and stick high temperature resistant tape on the edges of test plate 1#;

[0097] S2: Use a spraying robot, set the spraying temperature, humidity and parameters to be consistent with the on-site, adjust the spraying flow rate, and spray AR2000 040 paint (GTMC) to 20μm on test panels 1# and 2# respectively;

[0098] S3: After spraying, the paint was naturally leveled for 3 minutes, and then placed in an oven to preheat and flash-dry AR2000 040 paint (GTMC) at 40°C × 3 minutes, 50°C × 3 minutes, and 60°C × 3 minutes respectively;

[0099] S4: Take out the test board and cool it naturally at room temperature. At the same time, tear off the masking tape on the test board 1# and measure the mass of the test board 1#, which is recorded as m 2 ;

[0100] S5: Use a hand spray gun to spray the test coating on-site matching varnish MAC O-1820 CLEAR on test plate 2# and allow it to flow naturally for 5 minutes;

[0101] S6: Dry test plate 1# and test plate 2# at 140°C for 20 min and take them out;

[0102] S7: Measure the mass of test plate 1#, recorded as m 3 , calculate the flash-dried solids NV of the coating to be tested:

[0103] S8: Use a film thickness meter to measure the film thickness of the water-based automotive interior panel topcoat to be tested on test plate 1# to confirm whether it is 20μm;

[0104] S9: Observe the appearance of the paint film of test plate 2# to check whether the paint film has cracks, gloss loss or pinholes, and confirm whether the anti-cracking performance of the tested coating meets the construction requirements.

[0105] Table 4 Test results of anti-cracking performance of AR2000 040 paint (GTMC)

[0106]

[0107]

[0108] Note: △ indicates abnormal paint film, O indicates normal paint film

[0109] Through the above experimental results, the lower the preheating temperature of AR2000 040 paint (GTMC), the lower the flash-dry solid content, and the greater the risk of cracking in the paint film. After flash-drying at 60℃×3min, there is no risk of cracking when the film thickness of AR2000 040 paint (GTMC) is within 20μm.

[0110] Due to the poor hiding power of AR2000 040 paint (GTMC) and the thicker film thickness during on-site construction, the above test method was repeated, and the flash-drying conditions were fixed (60℃×3min). The limit value of the film thickness of the inner panel construction of AR2000 040 paint (GTMC) was determined. It was finally found that the paint film began to crack when the film thickness of the topcoat was 26μm. Therefore, the film thickness of the inner panel construction on site needs to be controlled within 26μm or the preheating conditions need to be improved to prevent cracking of the inner panel.

[0111] Table 5 Test results of cracking limit of AR2000 040 paint (GTMC)

[0112] Construction film thickness (μm) 24 26 Pre-baking conditions 60℃×3min 60℃×3min <![CDATA[m 1 (g)]]> 22.8136 22.9023 <![CDATA[m 2 (g)]]> 23.5043 23.7219 <![CDATA[m 3 (g)]]> 23.2439 23.3875 Flash dried solids (%) 62.3 59.2 Film thickness measured by film thickness meter (μm) 24 26 Cracking O △ Loss of Light O △ Pinhole O △

[0113] Note: △ indicates abnormal paint film, O indicates normal paint film

[0114] Example 3

[0115] The method for detecting the anti-cracking ability of the water-based automobile inner panel topcoat described in the present application is used to test the AR 3000 Zunhuang baking topcoat (BAIC) to determine the anti-cracking performance of the AR 3000 Zunhuang baking topcoat (BAIC), which specifically includes the following steps:

[0116] S1: Take two identical test plates, numbered as test plate 1# and test plate 2#, and measure the mass of test plate 1#, recorded as m 1 , and stick high temperature resistant tape on the edges of test plate 1#;

[0117] S2: Use a spraying robot, set the spraying temperature, humidity and parameters to be consistent with the site, adjust the spraying flow rate, and spray AR 3000 Zunhuang drying topcoat (BAIC) to 20μm on test panels 1# and 2# respectively;

[0118] S3: After spraying, the surface was naturally leveled for 3 minutes, and then placed in an oven to preheat and flash-dry AR 3000 Zunhuang baking topcoat (BAIC) at 40°C × 3 minutes, 50°C × 3 minutes, and 60°C × 3 minutes respectively;

[0119] S4: Take out the test board and cool it naturally at room temperature. At the same time, tear off the masking tape on the test board 1# and measure the mass of the test board 1#, which is recorded as m 2 ;

[0120] S5: Use a hand spray gun to spray the test panel 2# with the on-site matching varnish 2K high solid varnish (BAIC) and allow it to flow naturally for 8 minutes;

[0121] S6: Dry test plate 1# and test plate 2# at 140°C for 20 min and take them out;

[0122] S7: Measure the mass of test plate 1#, recorded as m 3 , calculate the flash-dried solids NV of the coating to be tested:

[0123] S8: Use a film thickness meter to measure the film thickness of the water-based automotive interior panel topcoat to be tested on test plate 1# to confirm whether it is 20μm;

[0124] S9: Observe the appearance of the paint film of test plate 2# to check whether the paint film has cracks, gloss loss or pinholes, and confirm whether the anti-cracking performance of the tested coating meets the construction requirements.

[0125] Table 6 Test results of anti-cracking performance of AR 3000 yellow baking topcoat (BAIC)

[0126] Construction film thickness (μm) 20 20 20 Pre-baking conditions 40℃×3min 50℃×3min 60℃×3min <![CDATA[m 1 (g)]]> 22.8171 22.9089 22.8268 <![CDATA[m 2 (g)]]> 23.4541 23.3993 23.2556 <![CDATA[m 3 (g)]]> 23.1056 23.2031 23.1188 Flash dried solids (%) 45.3 60.0 68.1 Film thickness measured by film thickness meter (μm) 20 20 20 Cracking △ O O Loss of Light △ O O Pinhole △ O O

[0127] Note: △ indicates abnormal paint film, O indicates normal paint film

[0128] Through the above experimental results, the lower the preheating temperature of AR 3000 Zunhuang baking topcoat (BAIC), the lower the flash-dry solid content, and the greater the risk of cracking in the paint film. After flash drying at 50℃×3min or 60℃×3min, there is no risk of cracking when the film thickness of AR 3000 Zunhuang baking topcoat (BAIC) inner plate is within 20μm.

[0129] Due to the poor hiding power of AR 3000 Zunhuang baking topcoat (BAIC) and the thick film thickness of on-site construction, the above-mentioned test method was repeated, the flash drying conditions were fixed (60℃×3min), and the limit value of the film thickness of the inner panel of AR 3000 Zunhuang baking topcoat (BAIC) was determined. It was finally found that cracks began to appear when the film thickness of the topcoat was 25μm. Therefore, the film thickness of the inner panel on-site construction needs to be controlled within 25μm or the preheating conditions need to be improved to prevent cracking of the inner panel.

[0130] Table 7 Test results of cracking limit of AR 3000 BAIC baking topcoat

[0131] Construction film thickness (μm) 23 25 Pre-baking conditions 60℃×3min 60℃×3min <![CDATA[m 1 (g)]]> 22.7891 22.8124 <![CDATA[m 2 (g)]]> 23.3152 23.4283 <![CDATA[m 3 (g)]]> 23.1216 23.1764 Flash dried solids (%) 63.2 59.1 Film thickness measured by film thickness meter (μm) 23 25 Cracking O △ Loss of Light O △ Pinhole O △

[0132] Note: △ indicates abnormal paint film, O indicates normal paint film

[0133] Example 4

[0134] The method for detecting the anti-cracking ability of the water-based automobile inner panel topcoat described in the present application is used to test AR 2300 plain red (BACH) to determine the anti-cracking performance of AR 2300 plain red (BACH), which specifically includes the following steps:

[0135] S1: Take two identical test plates, numbered as test plate 1# and test plate 2#, and measure the mass of test plate 1#, recorded as m 1 , and stick high temperature resistant tape on the edges of test plate 1#;

[0136] S2: Use a spraying robot, set the spraying temperature, humidity and parameters to be consistent with the on-site, adjust the spraying flow rate, and spray AR 2300 plain red (BACH) to 20μm on test panels 1# and 2#;

[0137] S3: After spraying, allow the surface to level naturally for 3 minutes, then place in an oven and preheat and flash dry AR 2300 plain red (BACH) at 40°C × 3 minutes, 50°C × 3 minutes, and 60°C × 3 minutes respectively;

[0138] S4: Take out the test board and cool it naturally at room temperature. At the same time, tear off the masking tape on the test board 1# and measure the mass of the test board 1#, which is recorded as m 2 ;

[0139] S5: Use a hand spray gun to spray the test panel 2# with the on-site matching varnish MAC O-1700 varnish (BACH), and allow it to flow naturally for 5 minutes;

[0140] S6: Dry test plate 1# and test plate 2# at 140°C for 20 min and take them out;

[0141] S7: Measure the mass of test plate 1#, recorded as m 3 , calculate the flash-dried solids NV of the coating to be tested:

[0142] S8: Use a film thickness meter to measure the film thickness of the water-based automotive interior panel topcoat to be tested on test plate 1# to confirm whether it is 20μm;

[0143] S9: Observe the appearance of the paint film of test plate 2# to check whether the paint film has cracks, gloss loss or pinholes, and confirm whether the anti-cracking performance of the tested coating meets the construction requirements.

[0144] Table 8 AR 2300 plain red (BACH) anti-cracking performance test results

[0145] Construction film thickness (μm) 20 20 20 Pre-baking conditions 40℃×3min 50℃×3min 60℃×3min <![CDATA[m 1 (g)]]> 22.8165 22.9012 22.8247 <![CDATA[m 2 (g)]]> 23.5284 23.4857 23.3282 <![CDATA[m 3 (g)]]> 23.0977 23.1835 23.1092 Flash dried solids (%) 39.5 48.3 56.5 Film thickness measured by film thickness meter (μm) 20 20 20 Cracking △ △ △ Loss of Light △ △ △ Pinhole △ △ △

[0146] Note: △ indicates abnormal paint film, O indicates normal paint film

[0147] The above experimental results show that the lower the preheating temperature of AR 2300 plain red (BACH), the lower the flash-dry solid content, and the greater the risk of cracking in the paint film. After flash-drying at 60℃×3min, cracks appeared on the inner plate of AR 2300 plain red (BACH) at a film thickness of 20μm.

[0148] Repeat the above test method, fix the flash drying conditions (60℃×3min), and measure the limit value of AR 2300 Plain Red (BACH). Finally, it is found that there is no risk of cracking when the topcoat film thickness is less than 18μm. Since AR 2300 Plain Red (BACH) has poor hiding power and the film thickness is too thick during on-site construction, in order to prevent cracking of the inner plate of AR 2300 Plain Red (BACH) on site, the AR 2300 Plain Red (BACH) formula or on-site preheating conditions need to be adjusted accordingly.

[0149] Table 9 Test results of crack limit of AR 2300 plain red (BACH)

[0150]

[0151]

[0152] Note: △ indicates abnormal paint film, O indicates normal paint film

[0153] Combined with the data in Tables 3 to 9, the lower the flash-dry solids of water-based automotive inner panel topcoat, the greater the risk of cracking in the inner panel paint film. The inner panel paint film cracks, and the flash-dry solids of water-based automotive inner panel topcoat are basically concentrated between 40% and 60%. When the flash-dry solids of water-based automotive inner panel topcoat is less than 60%, there is a risk of cracking, and there is also a risk of poor paint film such as loss of gloss and pinholes. In order to avoid poor appearance of the paint film, it is necessary to ensure that the flash-dry solids of water-based automotive inner panel topcoat are above 60%. Through the anti-cracking ability detection method of water-based automotive inner panel topcoat described in the present invention, the anti-cracking ability of the sample to be tested can be directly, quickly and accurately judged by simply testing the flash-dry solids of the sample to be tested. At the same time, the anti-cracking limit film thickness of the sample to be tested can also be accurately tested by the method described in the present invention.

[0154] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for detecting the anti-cracking performance of water-based automobile inner panel paint, characterized in that: The steps include: S1: Take the board to be tested, measure the mass of the board, record it as m1, and stick tape on the edges of the board. S2: Spray the water-based automotive interior panel topcoat to be tested on the surface of the test panel to the target film thickness; S3: After spraying, the paint will level naturally, and then the water-based automotive interior panel topcoat to be tested will be preheated and flash-dried; S4: After flash drying, tear off the tape on the test plate and measure the mass of the test plate, recorded as m2; S5: Dry the test plate. After drying, measure the mass of the test plate, record it as m3, and use the formula Calculate the flash-dry solids NV of the water-based automotive interior panel topcoat to be tested.

2. The detection method according to claim 1, characterized in that: The target film thickness is 18-26 μm.

3. The detection method according to claim 1, characterized in that: The time for natural leveling in step S3 is 2-5 minutes.

4. The detection method according to claim 1, characterized in that: The temperature of the preheat flash drying is 40-60° C., and the time of the preheat flash drying is 2-3 minutes.

5. The detection method according to claim 1, characterized in that: The drying conditions in step S5 are (140-160)°C×(15-30)min.

6. The detection method according to claim 1, characterized in that: The material of the test plate is selected from one of a hearing plate, an electrophoresis plate, a mid-coated plate, a cold-rolled steel plate and a tinplate plate.

7. The detection method according to claim 6, characterized in that: The size of the test plate is (70-100) mm*(150-200) mm.

8. The detection method according to claim 1, characterized in that: The detection method also includes determining whether the anti-cracking performance of the water-based automobile inner panel topcoat to be tested meets the on-site construction process requirements through the flash-dried solid content NV.

9. The detection method according to claim 8, characterized in that: The determination is: When the flash-dry solid content is less than 60%, the water-based automotive inner panel topcoat to be tested has at least one of cracking, gloss loss, and pinholes, and it is determined that the anti-cracking performance of the water-based automotive inner panel topcoat to be tested does not meet the on-site construction process requirements; When the flash-dry solid content is ≥60%, there is no cracking, gloss loss or pinholes in the tested water-based automobile inner panel paint, and it is determined that the anti-cracking performance of the tested water-based automobile inner panel paint meets the on-site construction process requirements.

10. Application of the detection method according to any one of claims 1 to 9 in evaluating the anti-cracking performance of water-based automobile interior panel paint.